Formulation of Instant Drink from (Moringa oleifera Lam.) and (Heterotrigona itama) using Foam Mat Drying Method - Desy Siska Anastasia; Sri Luliana; Nabila Mayang Ningrum (Majalah Obat Tradisional, 2025)
Moringa contains nutrients that benefit the food and health sectors. The part that has many benefits is the leaves. Moringa leaves contain the compound quercetin (flavonoid), which has antioxidant properties. Kelulut honey contains protocatechuic acid (PCA), which has potent antioxidant activity and OH groups to attract free radicals. The development of a functional drink from Moringa leaves and kelulut honey can be packaged more practically as an instant drink. This research aims to determine the physical characteristics, antioxidant activity, and panelists' preference level (hedonics) for instant drinks with variations of drying temperatures (50, 60, 70°C) and maltodextrin concentrations (15, 20, 30%). Instant drink uses the foam mat drying method with tween 80 as the foaming agent. The results showed that variations in temperature and concentration of maltodextrin influenced the physical characteristics of instant drinks with the best values for each test, which are water content (0.60%), flow time (1.68 g/sec), angle of repose (32°), tapping (6.08%), dissolution time in warm water (3.21 seconds). The best antioxidant activity value produced is 94.73% at 15% formula at 50°C temperature. The panelist's preference levels showed significant differences in smell, color, and taste, with the most preferred being the 15% formula.